Leading from the Middle: Lessons Learned for New Chairs - Christopher Jochum; Jared Rawlings (Academic Chairpersons Conference Proceedings, 2019)
In this session, two academic chairs will share lessons learned during their first years leading a department. This session will include advice related to faculty development, managing conflicts, academic accreditation, initiating new programs, working with higher administration and time management for active teacher-scholars.
Keywords: Departmental leadership; New chairs; Program development; Conflict management; Time management